Live and heat-killed Leuconostoc mesenteroides counteract the gastrointestinal dysfunction in chronic kidney disease mice through intestinal environment modulation. - Fittree Hayeeawaema; Natthawan Sermwittayawong; Chittipong Tipbunjong; Nawiya Huipao; Paradorn Muangnil; Pissared Khuituan (PLoS ONE)
Probiotics are well-known therapeutic agents for managing constipation and have been used to improve chronic kidney disease (CKD) progression. However, heat-killed probiotics on CKD remain inadequately explored. This study aimed to evaluate the probiotic potential of lactic acid bacteria derived from natural sources and to investigate the effects of both live and heat-killed Leuconostoc mesenteroides (Ln.m) on renal and gastrointestinal functions in CKD mice. Ln.m was selected from acid and bile salt intolerance tests, non-hemolytic activity, and antibiotic sensitivity. CKD mice demonstrated significantly elevated blood urea nitrogen (BUN) and creatinine levels compared to control mice (p < 0.001 and p < 0.01). Treatment with live and heat-killed Ln.m significantly reduced BUN and creatinine levels in CKD mice (p < 0.01 and p < 0.05). Additionally, kidney damage observed in CKD mice compared to control mice, including glomerular necrosis, tubular dilatation, inflammation, and fibrosis, was significantly alleviated following live and heat-killed Ln.m treatments. CKD-induced gastrointestinal dysfunction was characterized by an imbalance in Firmicutes/Bacteroidota populations, increased colonic uremic toxin (p < 0.01), reduced fecal short-chain fatty acids (SCFAs) (p < 0.05), and constipation. Treatment with live and heat-killed Ln.m restored gut microbiota, decreased uremic toxin (p < 0.001), increased SCFAs (p < 0.05), and alleviated constipation. In summary, both live and heat-killed Ln.m effectively alleviated gastrointestinal dysfunction and renal damage in CKD mice, primarily through modulation of the intestinal environment. These findings highlight the therapeutic potential of live and heat-killed Ln.m as the gastrointestinal dysfunction treatment in CKD.